Who Are the Scrooges? Personality Predictors of Holiday Spending - Weston, Sara J. (Soc Psychol Personal Sci, 2018)
The sharp increase in consumption over the holiday season has important economic implications, yet the psychology underlying this phenomenon has received limited attention. Here, we evaluate the role of individual differences in holiday spending patterns. Using 2 million transactions across 2,133 individuals, we investigate the relationship between the Big 5 personality traits on spending at Christmas. Zero-order correlations suggest holiday spending is associated with conscientiousness, neuroticism, and extraversion; the relationship with neuroticism persists after accounting for possible confounders including income and demographics. These results improve our understanding of how different personality traits predict how people respond to the environmental demands of the holiday season and have broader implications for how personality relates to consumer behavior.